Surgical and Peri-Operative Considerations for Brain Metastases - Gupta, Saksham; Dawood, Hassan; Giantini Larsen, Alexandra; Fandino, Luis; Knelson, Erik H.; Smith, Timothy R.; Lee, Eudocia Q.; Aizer, Ayal; Dunn, Ian F.; Bi, Wenya Linda (Frontiers in Oncology, 2021)
Introduction: Brain metastases are the most common brain tumors in adults, whose management remains nuanced. Improved understanding of risk factors for surgical complications and mortality may guide treatment decisions. Methods: A nationwide, multicenter analysis was conducted with a retrospective cohort. Adult patients in the 2012-2015 American College of Surgeons National Surgical Quality Improvement Project (ACS NSQIP) databases who received a craniotomy for resection of brain metastasis were included. Results: 3500 cases were analyzed, of which 17% were considered frail and 24% were infratentorial. The most common 30-day medical complications were venous thromboembolism (3%, median time-to-event [TTE] 4.5 days), pneumonia (4%, median TTE 6 days), and urinary tract infections (2%, median TTE 5 days). Reoperation and unplanned readmission occurred in 5% and 12% of patients, respectively. Infratentorial approach and frailty were associated with reoperation before discharge (OR 2.0 for both; p=0.01 and p=0.03 respectively), but not after discharge. Infratentorial approaches conferred heightened risk for readmission for hydrocephalus (OR 5.1, p=0.02) and reoperation for cerebrospinal fluid diversion (OR 7.1, p<0.001).Overall 30-day mortality was 4%, with nearly three-quarters occurring after discharge. Pre-frailty and frailty were associated with increased odds for post-discharge mortality (OR 1.7 and 2.7, p<0.05), but not pre-discharge mortality. We developed a model to identify pre-/peri-operative variables associated with death, including frailty, thrombocytopenia, and high American Society of Anesthesiologists score (AUROC 0.75). Conclusions: Optimization of metrics contributing to patient frailty and heightened surveillance in patients with infratentorial metastases may be considered in the peri-operative period.